2017
DOI: 10.1002/smi.2776
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of instrumental reminiscence intervention on improving coping in healthy older adults

Abstract: Reminiscence is a psychological intervention that uses the recall of past events, feelings, and thoughts to facilitate pleasure, quality of life, and adjustment to present life. The main goal of this study was to investigate the effect of a reminiscence intervention programme on coping strategies. One hundred fifty healthy older adults attended the reminiscence sessions. In order to evaluate the effects of the programme and find out if its effects lasted over time, we used an experimental design with pretest, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 29 publications
(43 reference statements)
2
26
0
4
Order By: Relevance
“…Teniendo en cuenta el análisis de las investigaciones que estudian variables adaptativas con intervención en Reminiscencia en el periodo analizado (2015-2020), observamos que la mayor parte de las investigaciones se realizan en comunidad (Allen, Doyle y Roche, 2020;Aşiret y Dutkun, 2018;Satorres, Viguer, Fortuna y Meléndez, 2018;Nakatsuka et al, 2016;Cho, 2016;Charlesworth et al, 2016;Meléndez, Fortuna, Sales y Mayordomo, 2015).…”
Section: Discussionunclassified
“…Teniendo en cuenta el análisis de las investigaciones que estudian variables adaptativas con intervención en Reminiscencia en el periodo analizado (2015-2020), observamos que la mayor parte de las investigaciones se realizan en comunidad (Allen, Doyle y Roche, 2020;Aşiret y Dutkun, 2018;Satorres, Viguer, Fortuna y Meléndez, 2018;Nakatsuka et al, 2016;Cho, 2016;Charlesworth et al, 2016;Meléndez, Fortuna, Sales y Mayordomo, 2015).…”
Section: Discussionunclassified
“…It has been confirmed that both the PASS and BCS positively predict outcome-based resilience (i.e., General Health Questionnaire; see Kalisch et al, 2020;Veer et al, 2020). Moreover, some of the subcomponents of the scales have also been linked frequently to positive (mental) health outcomes (Garnefski et al, 2001;Garnefski & Kraaij, 2006b;Kraaij et al, 2002;Nowlan et al, 2015;Raut et al, 2014), and have been shown to be modifiable (Garland et al, 2009;Hanley & Garland, 2014;Satorres et al, 2018). Yet, the exact relationships with QoL have not been investigated.…”
Section: Resilience Factorsmentioning
confidence: 90%
“…Por el contrario, las personas con PTL piensan menos en el futuro y el presente, y más en el pasado. Esto puede estar relacionado con el uso de la reminiscencia y la construcción de la memoria autobiográfica habitual en las personas mayores (Satorres, Viguer, Fortuna, & Meléndez, 2017). Por ejemplo, Leist, Ferring y Filipp (2010) examinaron el número de recuerdos autobiográficos positivos y negativos en una muestra de adultos y mayores (de 41 a 86 años).…”
Section: La Percepción Del Tiempo Limitadounclassified